(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes and investigates the skills of Alisher Navoi in takhmis creativity and the artistic properties of the poet’s takhmis. It analyzes «takhmisi hud» (private takhmis) of Navoi written on one of his gazelles.